2011
DOI: 10.1093/rheumatology/ker284
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and ultrasonography assessment of peripheral enthesitis in ankylosing spondylitis

Abstract: PDUS permits detection of structural and inflammatory abnormalities of the enthesis in AS and may complement the physical examination in order to better evaluate enthesitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 20 publications
3
41
0
12
Order By: Relevance
“…Hamdi et al 99 reported correlation with clinical enthesis indices (Maastricht Ankylosing Spondylitis Score, Spondyloarthritis Research Consortium of Canada (SPARCC) Enthesitis Index), while two studies reported no correlation 39 98. Two studies reported discrepancies in abnormal entheses detected by US versus clinical examination 40 105…”
Section: Resultsmentioning
confidence: 99%
“…Hamdi et al 99 reported correlation with clinical enthesis indices (Maastricht Ankylosing Spondylitis Score, Spondyloarthritis Research Consortium of Canada (SPARCC) Enthesitis Index), while two studies reported no correlation 39 98. Two studies reported discrepancies in abnormal entheses detected by US versus clinical examination 40 105…”
Section: Resultsmentioning
confidence: 99%
“…Several published studies have reported significantly higher enthesitis scores in the US assessed groups in comparison to the groups evaluated only by clinical examination. US assessment was made in grey scale alone or combined with Doppler mode, for lower and or upper limbs [3,6,[27][28][29][30][31]33,35,62,63,66,69,78] .…”
Section: Subclinical Enthesitismentioning
confidence: 99%
“…In the latter years, new imaging modalities such as magnetic resonance imaging (MRI) and ultrasound (US) have been developed, offering a direct visualization of the enthesis and enthesal-related structures. Subsequently, an earlier and a more accurate, inflammatory and structural lesion detection in symptomatic and asymptomatic entheseal areas is expected [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Among them is ankylosing spondylitis (AS), in which enthesitis of the heel is common and occasionally is responsible for their initial symptom to seek clinics [2]. Enthesitis is defined as inflammation at the bony interfaces of ligaments, tendons, aponeurosis, annulus fibrosus and joint capsules [3]. Because many of such structures originate from, are inserted in, and also pass alongside the calcaneus, heel pain is frequent peripheral symptom in AS patients from enthesitis of inferior and posterior calcaneus [1,4,5].…”
Section: Introductionmentioning
confidence: 99%